STUDI EKSPERIMENTAL PERFORMANSI SISTEM KOLEKTOR SURYA JENIS PALUNG SILINDRIS DENGAN ABSORBER MULTI-PIPA - Wibowo, Hary (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2005)
Solar collector cylindrical troughs with multi pipe absorbers were observed to find the best collector performance. The research put on two types collector arrangements, that are series and parallel arrangement. There are three type configurations of absorber pipes consisting of 3, 4 , and 6 pipes. The objective of this research is to find a simple construction of solar collector that produce high temperature working fluid. Three collectors were observed simultaneously. Each collector installed a type configuration and a type arrangement. Water flow rates in this experimental were 50, 125, 175, and 300 cc/minute. Observation on three collectors was done on the same ti-me, condition, and flow. Data of observation result used to calculate actual and ideal co-llector efficiency. The results are presented in table and graphic to be analyzed. Results of calculation indicate the collector efficiency on each absorber pipe ar-rangement and configuration. The higher collector efficiency on series arrangement, is 0.763, that was resulted from collector with 3 pipe configuration in 175 cc/minute debit of flow. The higher collector efficiency on parallel arrangement, is 0.491, also resulted from the collector with 3 pipe configuration in 175 cc/minute debit of flow too. The final con-clusion, collector 3 pipe configuration in series arrangement with 175 cc/minute debit of flow is the best collector cylindrical trough in this research.